Heat advection processes leading to El Niño events as depicted by an ensemble of ocean assimilation products. Issue 6 (2nd June 2016) - Ballester, Joan; Bordoni, Simona; Petrova, Desislava; Rodó, Xavier
Abstract: The oscillatory nature of El Niño‐Southern Oscillation results from an intricate superposition of near‐equilibrium balances and out‐of‐phase disequilibrium processes between the ocean and the atmosphere. The main objective of the present work is to perform an exhaustive spatiotemporal analysis of the upper ocean heat budget in an ensemble of state‐of‐the‐art ocean assimilation products. We put specific emphasis on the ocean heat advection mechanisms, and their representation in individual ensemble members and in the different stages of the ENSO oscillation leading to EN events. Our analyses consistently show that the initial subsurface warming in the western equatorial Pacific is advected to the central Pacific by the equatorial undercurrent, which, together with the equatorward advection associated with anomalies in both the meridional temperature gradient and circulation at the level of the thermocline, explains the heat buildup in the central Pacific during the recharge phase. We also find that the recharge phase is characterized by an increase of meridional tilting of the thermocline, as well as a southward upper‐ocean cross‐equatorial mass transport resulting from Ekman‐induced anomalous vertical motion in the off‐equatorial regions. Although differences between data sets are generally small, and anomalies tend to have the same sign, the differences in the magnitude of the meridional term are seen to be key for explaining the different propagation speed of the subsurface warming tendency along the thermocline. The only exception is GECCO, which does not produce the patterns of meridional surface Ekman divergence (subsurface Sverdrup convergence) in the western and central equatorial Pacific. Key Points: We describe the representation of heat advection in individual assimilation products The recharge phase is characterized by upper‐ocean cross‐equatorial mass transport Differences are small but GECCO does not correctly reproduce the meridional divergence